Screen printed gold electrode for bacteria panicle blight detection from in silico designed aptamers - Jumali, Siti Sarah; Mohamad Jamali, Muhamad Arif; Amir Hamzah, Amir Syahir (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Bacteria Panicle Blight (BPB) is a newly emerging disease of paddy caused by Burkholderia glumae. Its devastating effect to paddy is owed to the pathogenicity of toxoflavin that is produced by the bacterium through the assistance of sequential protein expression event. Usually, the detection is made by manual observation or sending them to the laboratory for testing. These methods are quite laborious and time consuming for immediate action. Usually, real time sensors require antibody for the disease detection which may be costly and produce inconsistent results. In this study, aptamers are used as capturing agents in place of traditional antibody methods. Also, the selected aptamers were innovatively designed in silico, unlike the conventional SELEX method that is costly, laborious and time consuming. After screening 33 aptamers through molecular docking, 4 were objected to molecular dynamics simulation and MM-PBSA to predict binding properties. Through computational results, the aptamer candidates exhibited lowest docking energy and best interaction when simulated at 200nanoseconds and when tested experimentally, they give high affinity towards target protein. This innovation may cut short the time needed to develop drugs and sensing agents while having high commercialization potential as the only material it needs is a high-end computer.